The Prognostic Significance of the Continuous Administration of Anti-PD-1 Antibody via Continuation or Rechallenge After the Occurrence of Immune-Related Adverse Events - Fujisaki, Toshiya; Watanabe, Satoshi; Ota, Takeshi; Kushiro, Kohei; Sato, Yusuke; Takahashi, Miho; Ohtsubo, Aya; Shoji, Satoshi; Nozaki, Koichiro; Ichikawa, Kosuke; Hokari, Satoshi; Kondo, Rie; et al. (Frontiers in Oncology, 2021)
Objectives: Although immune checkpoint inhibitors (ICIs) have been shown to improve overall survival (OS) in advanced non-small-cell lung cancer (NSCLC) patients, ICIs sometimes cause various types of immune-related adverse events (irAEs), which lead to the interruption of ICI treatment. This study aims to evaluate the clinical significance of the continuation of ICIs in NSCLC patients with irAEs and to assess the safety and efficacy of the readministration of ICIs after their discontinuation due to irAEs. Methods: We retrospectively identified patients with advanced NSCLC who were treated with 1st- to 3rd-line anti-PD-1 therapy from January 2016 through October 2017 at multiple institutions belonging to the Niigata Lung Cancer Treatment Group. Progression-free survival (PFS) and OS from the initiation of ICI treatment were analyzed in patients with and without irAEs, with and without ICI interruption, and with and without ICI readministration. A 6-week landmark analysis of PFS and OS was performed to minimize the lead-time bias associated with time-dependent factors. Results: Of 231 patients who received anti-PD-1 antibodies, 93 patients (40%) developed irAEs. Of 84 eligible patients with irAEs, 32 patients (14%) continued ICIs, and OS was significantly longer in patients who continued ICIs than in patients who discontinued ICIs (not reached (95% CI: NE-NE) vs. not reached (95% CI: 22.4-NE); P = 0.025). Of 52 patients who discontinued ICIs, 14 patients (6.1%) readministered ICIs, and OS in patients with ICI readministration was significantly longer than in patients without ICI readministration (not reached (95% CI: NE-NE) vs. not reached (95% CI: 8.4-NE); P = 0.031). Conclusion: The current study demonstrated that both the continuation and readministration of ICIs after irAE occurrence improved OS compared to the permanent interruption of ICIs in NSCLC patients with ICI-related irAEs.